(untitled) (International Conference on Education, Psychology and Humanities, 2026)
This article highlights the application of knowledge acquired by students in various life situations when teaching natural sciences in general education based on a competency-based approach, existing curricula, methodological aspects and approaches to teaching, students’ creative and critical thinking skills, their ability to apply acquired knowledge in life, the content of teaching, its theoretical and practical significance, professional activity, didactic levels, and methodological aspects of developing this process.